Borax Content of Meatballs in Market X Area Surabaya Indonesia - Liza Fajrin Zukrisningtyas; Narwati Narwati; Pratiwi Hermiyanti; Marlik Marlik; Seow Ta Wee (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Borax was still utilized in the process of making food, one of which was making meatballs. Meatball traders added borax to extend the short shelf life of meat and increase the chewy texture, as well as to give the meatballs a more white color. The research objective was to analyze the borax content of meatball samples in market X Surabaya, Indonesia in 2023. Analytical observational research method, the variables studied were the physical quality of meatballs and the borax content in meatballs. The object of this research was 12 meatballs sold by all vendors in Market X Surabaya, Indonesia. The results of the organoleptic test researched obtained 4 meatball samples (34%) with good assessment criteria, most of the 7 meatball samples (58%) with sufficient assessment criteria, and 1 meatball sample (8%) with poor assessment criteria. Laboratory test results 1 meatball sample (8%) contained borax, with physical characteristics of chewy texture, pale gray color, tart taste, and fishy smell. The conclusion of this studied was that 1 out of 12 samples had physical characteristics of meatballs containing borax and borax content was related to the organoleptic test with a significant valued of p-value = 0. 032. Suggestions for traders to used alternative ingredients to replaced borax, namely carrageenan (seaweed) to improved the physical quality of meatballs in terms of texture, color, and smell.